High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.

Highly stable COF-supported Co/Co(OH)(2) nanoparticles heterogeneous catalyst for reduction of nitrile/nitro compounds under mild conditions - Mullangi, Dinesh; Chakraborty, Debanjan; Pradeep, Anu; Koshti, Vijay; Vinod, Chathakudath P.; Panja, Soumendranath; Nair, Sunil; Vaidhyanathan, Ramanathan (Small, 2018)
Ordered nanoporosity in covalent organic framework (COF) offers excellent opportunity for property development. Loading nanoparticles (nPs) onto them is one approach to introducing tailor-made properties into a COF. Here, a COF-Co/Co(OH)(2) composite containing about 16 wt% of <6 nm sized Co/Co(OH)(2) nPs is prepared on a N-rich COF support that catalyzes the release of theoretical equivalence of H-2 from readily available, safe, and cheap NaBH4. Furthermore, the released H-2 is utilized for the hydrogenation of nitrile and nitro compounds to amines under ambient conditions in a facile one-pot reaction. The COF "by choice" is built from "methoxy" functionalized dialdehydes which is crucial in enabling the complete retention of the COF structure under the conditions of the catalysis, where the regular Schiff bonds would have hydrolyzed. The N-rich binding pockets in the COF ensure strong nP-COF interactions, which provides stability and enables catalyst recycling. Modeling studies reveal the crucial role played by the COF in exposing the active facets and thereby in controlling the activation of the reducing agent. Additionally, via density functional theory, we provide a rational explanation for how these COFs can stabilize nanoparticles which grow beyond the limiting pore size of the COF and yet result in a truly stable heterogeneous catalyst - a ubiquitous observation. The study underscores the versatility of COF as a heterogeneous support for developing cheap and highly active nonnoble metal catalysts.

Ag nanoparticles supported on a resorcinol-phenylenediamine-based covalent organic framework for chemical fixation of CO2 - Chakraborty, Debanjan; Shekhar, Pragalbh; Singh, Himan Dev; Kushwaha, Rinku; Vinod, C. P.; Vaidhyanathan, Ramanathan (Chemistry-An Asian Journal, 2019)
Covalent organic frameworks are a new class of crystalline organic polymers possessing a high surface area and ordered pores. Judicious selection of building blocks leads to strategic heteroatom inclusion into the COF structure. Owing to their high surface area, exceptional stability and molecular tunability, COFs are adopted for various potential applications. The heteroatoms lining in the pores of COF favor synergistic host-guest interaction to enhance a targeted property. In this report, we have synthesized a resorcinol-phenylenediamine-based COF which selectively adsorbs CO2 into its micropores (12 angstrom). The heat of adsorption value (32 kJ mol(-1)) obtained from the virial model at zero-loading of CO2 indicates its favorable interaction with the framework. Furthermore, we have anchored small-sized Ag nanoparticles (approximate to 4-5 nm) on the COF and used the composite for chemical fixation of CO2 to alkylidene cyclic carbonates by reacting with propargyl alcohols under ambient conditions. Ag@COF catalyzes the reaction selectively with an excellent yield of 90 %. Recyclability of the catalyst has been demonstrated up to five consecutive cycles. The post-catalysis characterizations reveal the integrity of the catalyst even after five reaction cycles. This study emphasizes the ability of COF for simultaneous adsorption and chemical fixation of CO2 into corresponding cyclic carbonates.
Keywords: CO2 capture; covalent organic frameworks; cyclic carbonates; Propargyl alcohols; silver nanoparticles

Aqueous-phase differentiation and speciation of Fe3+ and Fe2+ using water-stable photoluminescent lanthanide-based metal-organic framework - Maity, Rahul; Chakraborty, Debanjan; Nandi, Shyamapada; Yadav, Ankit Kumar; Mullangi, Dinesh; Vinod, C. P.; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2019)
Fe2+ is vital to O-2 transportation and photosynthesis regulated by oxidases and reductases. On the other hand, Fe3+ is detrimental due to its irreversible binding to O-2. Hence there is a need for selective identification of Fe3+ from aqueous systems in the presence of Fe2+. However, given their close chemical nature, it is not straightforward to differentiate them. Fe2+ and Fe3+ are typically sensed and differentiated using magnetic measurements, Mossbauer, X-ray absorption spectroscopy, or EXAFS, which are complex and equipment intensive techniques. In comparison, the fluorescence technique is advantageous in terms of time and accessibility. Although readily available lanthanide salts exhibit fluorescence, they are weak, and to serve as an optical probe, their luminescence has to be enhanced via ligand design. Hence we have designed a chromophoric ligand that can covalently bind to lanthanides and enhance its fluorescence intensity, and it binds selectively to Fe3+ through its nitrogen centers. It detects Fe3+ from low concentration (similar to 100 mu M) aqueous solutions, with fast response time (<1 min) and with a detection limit of 3.6 ppm. Importantly, the Fe3+ adsorbed MOF can be readily reactivated for the next cycle by merely washing with an aqueous ascorbic acid solution and can be used for multiple cycles without any appreciable loss in activity. This makes the Ln-MOF an environmentally benign, cost-effective, scalable, and recyclable probe.
Keywords: Fe3+ differentiation and speciation; flexible ligand; fluorescent MOF; iron speciation; Metal-organic framework; water sorption

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Cu/Cu2O nanoparticles supported on a phenol-pyridyl COF as a heterogeneous catalyst for the synthesis of unsymmetrical diynes via glaser-hay coupling - Chakraborty, Debanjan; Nandi, Shyamapada; Mullangi, Dinesh; Haldar, Sattwick; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (ACS Applied Materials & Interfaces, 2019)
Covalent organic frameworks (COFs) are a new class of porous crystalline polymers with a modular construct that favors fiinctionalization. COF pores can be used to grow nanoparticles (nPs) with dramatic size reduction, stabilize them as dispersions, and provide excellent nP access. Embedding substrate binding sites in COFs can generate host-guest synergy, leading to enhanced catalytic activity. In this report, Cu/Cu2O nPs (2-3 nm) are grown on a COF, which is built by linking a phenolic trialdehyde and a triamine through Schiff bonds. Their micropores restrict the nP to exceptionally small sizes (similar to 2-3 nm), and the pore walls decorated with strategically positioned hydrogen-bonding phenolic groups anchor the substrates via hydrogen-bonding, whereas the basic pyridyl sites serve as cationic species to stabilize the [CuclusterCl2](2-) type reactive intermediates. This composite catalyst shows high activity for Glaser-Hay heterocoupling reactions, an essential 1,3-diyne yielding reaction with widespread applicability in organic synthesis and material science. Despite their broad successes in homocoupled products, preparation of unsymmetrical 1,3-diynes is challenging due to poor selectivity. Here, our COF-based Cu catalyst shows elevated selectivity toward heterocoupling product(s) (Cu nP loading 0.0992 mol %; turn over frequency: similar to 4S-50; turn over number: similar to 17S-190). The reversible redox activity at the Cu centers has been demonstrated by carrying out X-ray photoelectron spectroscopy on the frozen reactions, whereas the crucial interactions between the substrates and the binding sites in their optimized configurations have been modeled using density functional theory methods. This report emphasizes the utility of COFs in developing a heterogeneous catalyst for a truly challenging organic heterocoupling reaction.
Keywords: Copper nanoparticles; Covalent organic framework; Glaser-Hay heterocoupling; heterogeneous catalysis; unsymmetrical diynes

Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF

Coordination flexibility aided CO2-specific gating in an iron isonicotinate MOF - Singh, Himan Dev; Nandi, Shyamapada; Chakraborty, Debanjan; Singh, Kirandeep; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Chemistry-an Asian Journal, 2022)
Coordination flexibility assisted porosity has been introduced into an Iron-isonicotinate metal-organic framework (MOF), (Fe(4-PyC)(2) . (OH). The framework showed CO2-specific gate opening behavior, which gets tuned as a function of temperature and pressure. The MOF ` s physisorptive porosity towards CO2, CH4, and N-2 was investigated; it adsorbed only CO2 via a gate opening phenomenon. The isonicotinate, representing a borderline soft base, is bound to the hard Fe3+ centre through monodentate carboxylate and pyridyl nitrogen. This moderately weak binding enables isonicotinate to spin like a spindle under the CO2 pressure opening the gate for a sharp increase in CO2 uptake at 333 mmHg (At 298 K, the CO2 uptake increases from 0.70 to 1.57 mmol/g). We investigated the MOF ` s potential for CO2/N-2 and CO2/CH4 gas separation aided by this gating. IAST model reveals that the CO2/N-2 selectivity jumps from 325 to 3131 when the gate opens, while the CO2/CH4 selectivity increases three times. Interestingly, this Fe-isonicotinate MOF did not follow the trend set by our earlier reported Hard-Soft Gate Control (established for isostructural M2+-isonicotinate MOFs (M=Mg, Mn)). However, we account for this discrepancy using the different oxidation state of metals confirmed by X-ray photoelectron spectroscopy and magnetism.
Keywords: CO2 capture; flexible MOF; gating; Isonicotinic

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.